Pengaruh Pola Asuh Orangtua dan Kebiasaan Belajar terhadap Prestasi Belajar Fisika - Bulan Amalia; Supardi Supardi (PANDITA : Interdisciplinary Journal of Public Affairs, 2023)
The purpose of this study was to determine the effect of parenting and study habits on physics learning achievement of students of class XI IPA SMAN 2 Cibinong in the 2010/2011 academic year. This research is a quantitative research. The data collection tool used is a survey by distributing questionnaires of parenting and study habits to students. The results of this study are in the form of numbers that have been processed. The data used in this study were taken from questionnaires and the odd semester report card results of the 2010/2011 school year. Parenting and study habits of students have a positive influence on the physics learning achievement of students at school. That is, the better the parenting style and learning habits of students, the better the physics learning achievement of students at school.Keywords: parenting, study habits, physics learning achievement